2015
DOI: 10.1155/2015/204127
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Electromagnetic Boundaries via Metasurfaces: From Theory and Fabrication to Functional Devices

Abstract: As two-dimensional metamaterials, metasurfaces have received rapidly increasing attention from researchers all over the world. Unlike three-dimensional metamaterials, metasurfaces can be utilized to control the electromagnetic waves within one infinitely thin layer, permitting substantial advantages, such as easy fabrication, low cost, and high degree of integration. This paper reviews the history and recent development of metasurfaces, with particular emphasis on the theory and applications relating to the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 268 publications
1
25
0
Order By: Relevance
“…As two-dimensional (2D) metamaterials, metasurfaces have been demonstrated to be able to achieve full control of the amplitudes, phases and polarization states of electromagnetic waves 1 2 . With gradient phase retardation across the metasurface, it was shown that the ancient optical law should be recast into a more general form 3 4 .…”
mentioning
confidence: 99%
“…As two-dimensional (2D) metamaterials, metasurfaces have been demonstrated to be able to achieve full control of the amplitudes, phases and polarization states of electromagnetic waves 1 2 . With gradient phase retardation across the metasurface, it was shown that the ancient optical law should be recast into a more general form 3 4 .…”
mentioning
confidence: 99%
“…Metasurfaces are thin planar arrays of resonant subwavelength elements arranged in a periodic or aperiodic (even random) manner which modifies boundary conditions for impinging optical waves in order to realize specific wave shaping. In recent years, metasurfaces have attracted progressively increasing attention and have become a rapidly growing field of research, due to their remarkable ability in manipulating electromagnetic (EM) waves, their versatility, and their ease of on-chip fabrication and integration [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Such metasurfaces can mimic bulk optics since they are capable of engineering the phase front of reflected and/or refracted optical waves at will.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the propagations and characteristics of metamaterial are significantly different from those of isotropic materials [3][4][5][6][7][8][9][10][11][12][13][14][15]. Metamaterial has many unusual properties and may lead to important applications, such as absorber [16], wave splitter [17], and subwavelength rectangular cavity [18].…”
Section: Introductionmentioning
confidence: 99%